Fruits basket. 7 - Takaya, Natsuki, 1973- (Fruits Basket Collectors Edition, 2016)
Yuki, alongside his mother, who already has his life after high school all mapped out, confronts his future at a parent-teacher conference. To make matters worse, when Yuki recalls buried memories, he becomes speechless! Meanwhile, Tohru pays a visit to the Sohma compound in order to confirm whether Kureno Sohma is really the same man with whom her best friend, Uo-chan, is in love! Love isn't in the air for Isuzu and Hatsuharu, however, as the two have broken up. Desperately in search of something, Isuzu visits Shigure's house as if driven there but collapses upon arrival. A shocked Tohru happens to be on the scene, but all she can do is comfort Isuzu in her pain. But Isuzu seems to know all about Tohru fighting the Sohma curse on her own.